KEBIJAKAN HUKUM PIDANA TERHADAP PENANGGULANGAN TINDAK PIDANA PENYELUNDUPAN MANUSIA DI INDONESIA - Gusniardy, Raja Thesa; Jayakusuma, Zulfikar; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
People smuggling is transnational organized and has had a negative impact onvarious countries as Indonesia's transit. People smuggling is an additional problem inaddition to the immigration problem, and is still increasing the funds needed to tacklethe problem of people smuggling in Indonesia, or what is known as a crime policy.The purpose of this thesis discussion, namely: First, to find answers to currentlegal policies in the handling of criminal acts of people smuggling in Indonesia. Second,to find the concept of struggle that can be proposed in the renewal of legal policiesagainst the prevention of people smuggling in Indonesia. This type of research used inthis study is normative legal research. Data sources used are secondary data sourcesobtained from the literature, including published official documents, books, legaljournals and so on.From the results of the study, it can be concluded the main thing. First, the legalpolicy in tackling the crime of people smuggling in Indonesia is still a lot of weaknesses.Article 120 of Law Number 6 of 2011 concerning Immigration has not been able tocover all aspects of handling human smuggling. Secondly, the concept that can beagreed upon in legal reforms in dealing with acts of people smuggling in Indonesia isby establishing laws and regulations governing people smuggling in order to securelegal certainty (the principle of legality) in Indonesia.Keywords: Criminal Law Policy - Prevention - People Smuggling